THE EFFORTS OF CHEMISTRY EDUCATION STUDENTS IN PREPARING TO BECOME PROFESSIONAL TEACHERS IN THE FUTURE - Sri Winarni; Syahrial Syahrial (JCER (Journal of Chemistry Education Research), 2023)
The purpose of this study is to map the efforts made by students of prospective chemistry teachers in preparing themselves to become professional teachers in the future. This research is naturalistic and is a case study. This research is carried out naturally during the ongoing lecture program (natural setting). The research was carried out when students took part in professional educational lectures in the intermediate semester of 2022. The research participants consisted of 17 chemistry education students. As the main instrument, researchers are a lecturer of professional education courses. Data is collected through documentation methods in the form of essays and then analyzed and interpreted qualitatively. The research results include student activities following professional, pedagogical, social, and personality competence. The most activity is related to pedagogic competence, while the lowest is related to social and professional competence. Needs to be developed grows activities that follow the four competencies proportionally in prospective teacher students. For students' social and professional competence, prospective chemistry teachers are generally at a stage that still needs improvement.